Utilization of Digital Content in Promotional Efforts at Juma Lau Nature Tourism, Sibolangit District, Deli Serdang Regency - Yeni Rachmawati; Zubaidah Hanum; Ekatri Ayuningsih; Asmaul Husna (Jurnal Masyarakat Indonesia (Jumas), 2024)
This study was conducted to provide a view that the use of technology in the digital era is very important in supporting tourism businesses. Many digital platforms can be used to promote tourism businesses such as Instagram, Facebook, YouTube and others. The use of digital platforms also needs to be supported by interesting content so that it can attract potential customers. The use of photos or images can also make the content more interesting. Juma Lau Nature Tourism located in Sibolangit District, Deli Serdang Regency is one of the tours that has the potential to further increase its visitors by using digital content.